Analisis Framing Surat Kabar Sinar Hindia, Sin Po dan Java Bode terhadap Protes Sosial Petani di Tangerang 1924 - Saka Tri Utama; Muhammad Wildan Hasan (Faculty of Adab and Humanities, Syarif Hidayatullah State Islamic University of Jakarta, 2023)
This study discusses the framing of Sinar Hindia, Sin Po, and Java Bode in reporting a peasant social protest in Tangerang in 1924. By using framing and mass sociology approach, this study tries to answer how the ideology of the newspapers Sinar Hindia, Sin Po, and Java Bode is manifested in reporting the social protests of farmers in Tangerang. The Sinar Hindia newspaper, which has an affiliation with socialist movement figures, framed the Tangerang incident by putting forward a narrative about the economic and social milieus of the indigenous population. The Sin Po newspaper, which was represent the voice of peranakan Tionghoa in the Dutch East Indies, adhered to the values of Tionghoa nationalism as its ideology in framing the events in Tangerang caused by religious doctrine carried out by the Kaiin Bapa Kayah group. The Java Bode newspaper, was represent with the wave of liberalism in the Dutch East Indies along with an editor who had a liberal-moderate understanding and judged that the events in Tangerang occurred based on the religious doctrine of the farmers.Abstrak: Penelitian ini membahas framing surat kabar Sinar Hindia, Sin Po dan Java Bode dalam memberitakan protes sosial petani di Tangerang pada tahun 1924. Dengan menggunakan teori analisis framing dan pendekatan sosiologi massa, penelitian ini berusaha menjawab bagaimana pengejahwantahan ideologi surat kabar Sinar Hindia, Sin Po dan Java Bode dalam mewartakan protes sosial petani di Tangerang. Surat kabar Sinar Hindia yang memiliki afiliasi dengan tokoh pergerakan sosialis memframing peristiwa Tangerang dengan mengedepankan narasi tentang kehidupan ekonomi dan sosial penduduk pribumi yang sangat memprihatinkan hingga membuat mereka harus melakukan protes tersebut. Surat kabar Sin Po yang hadir sebagai suara dari peranakan Tionghoa di Hindia Belanda, memegang teguh nilai-nilai nasionalisme Tionghoa sebagai ideologinya dalam memframing bahwa peristiwa di Tangerang diakibatkan oleh doktrin keagamaan yang dilakukan oleh kelompok Kaiin Bapa Kayah. Surat kabar Java Bode hadir bersama gelombang liberalisme di Hindia Belanda beserta redaktur yang berpemahaman liberal-moderat dan menilai bila peristiwa di Tangerang terjadi berdasarkan doktrin keagamaan para petani.